Cultural heritage protection issues in Leśnica, the settlement of Wrocław = Problemy ochrony dziedzictwa kulturowego osiedla Leśnica we Wrocławiu - Kononowicz, Alena (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Leśnica, today the settlement on the western edge of Wrocław, formerly was an independent town, located on a previously wooded area, with a linear street system. It developed in the Middle Ages around the castle and church playing a service role for the Silesian Piast court on their way to Legnica and during hunting. In the thirteenth century it received city rights, and lost them in the eighteenth century.
Keywords: osiedle mieszkaniowe; Wrocław; Leśnica; dawne miasteczko; ochrona dziedzictwa; rewitalizacja; settlement; heritage protection; revitalisation